Preparation, characterization and catalytic performance of mesoporous Ga and Ga-Al oxides - Michorczyk, Piotr; Kuśtrowski, Piotr; Kolak, Agnieszka; Żurek, Krzysztof (Видавництво Львівської політехніки, 2012)
Mesoporous Ga- and Ga-Al oxides were prepared by nanoreplication technique using CMK-3 matrix as a rigid template. The catalytic performance of mesoporous Ga2O3 and mixed Ga2O3-Al2O3 materials were investigated in the dehydrogenation of propane to propene with CO2 at 823 K.
Keywords: nanoreplication; gallium-alumina oxides; dehydrogenation; propene; carbon dioxide